Association of macrophage migration inhibitory factor gene polymorphisms with chronic periodontitis in a South Eastern Iranian population - Zahra Heidari; Hamidreza Mahmoudzadeh-Sagheb; Mohammad Hashemi; Somayeh Ansarimoghaddam; Bita Moudi; Nadia Sheibak (Wolters Kluwer Medknow Publications, 2017)
Background: Macrophage migration inhibitory factor (MIF) is a key proinflammatory mediator. It plays a vital role in immune response against the oral disease. MIF is a regulator of innate immunity, and bacterial antigens can stimulate serum level of this protein. In experimental gingivitis, the expression level of MIF increases and this increment positively correlates with oral plaque index. The single nucleotide polymorphisms in the gene encoding the MIF protein can control the function of MIF. The aim of the present study was a clarification of the associations between MIF-173 G/C, MIF 95 bp, and 189 bp insertion/deletion (I/D) polymorphisms and chronic periodontitis (CP) compared with healthy controls. Materials and Methods: This case-control study was carried out on 210 CP patients and 100 normal subjects. MIF-173 G/C and MIF 95 bp and 189 bp I/D polymorphisms were genotyped, using polymerase chain reaction-restriction fragment-length polymorphism (PCR-RFLP) and PCR, respectively. Allele and genotype frequencies of the variants were compared between patients and controls using Chi-square. test. The value of P < 0.05 was considered statistically significant. Results: The study findings showed that MIF-173 G/C polymorphism, especially the C allele increased the risk of CP. The 95-bp I/D polymorphism was not associated with CP and the 185-bp I/D variant was not polymorphic in our population. Conclusion: Therefore, MIF-137 G/C variant increased the risk of CP in the South East of the Iranian population. In other words, polymorphisms in MIF gene influence clinical outcome of CP infection and influence the susceptibility to disease. Further studies with larger sample sizes and different ethnicities are required to validate our findings.